Tele-revista y la Transición : un programa de la televisión suiza para emigrantes españoles (1973-1989) - Calvo Salgado, Luis M.; Langa Nuño, Concha; Prieto Lopez, Moises (Madrid : Iberoamericana, 2015)
Tele-revista, a Swiss TV news program, was broadcasted in Spanish for Spanish emigrants living in Switzerland.
Includes bibliographical references and index.
Online resource; title from PDF title page (Digitalia, viewed October 22, 2019)
Keywords: Tele-revista (Television program); Spain -- History -- 20th century -- Press coverage; Television broadcasting of news -- Switzerland; Ethnic television broadcasting -- Switzerland; Spaniards -- Switzerland.d; Electronic books